Implementasi Kecerdasan Buatan dalam Penciptaan Video Pembelajaran Bahasa Inggris tentang Komunikasi Self-Introduction bagi Mahasiswa Perhotelan - Tyas, Maharani Ayuning (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
This study aims to explore the role of artificial intelligence (AI) in the creation of English learning videos on the topic of self-introduction communication for hospitality students. This study uses a descriptive qualitative approach with a focus on case studies. Data collection was carried out using documentation study methods, interviews and observations. The process of making learning videos is carried out through three stages including pre-production, production and post-production. The results of this study indicate that the use of artificial intelligence technology can help the effectiveness of time and efficiency of human resources in the production process. In addition, the quality of the visuals and audio produced is able to meet the standards of the needs of attractive audio-visual learning media. In conclusion, artificial intelligence technology has a significant role in the production process and creation of self-introduction communication English learning videos.